PENGARUH KARAKTERISTIK KOMITE AUDIT, INDEPENDENSI DEWAN KOMISARIS, REPUTASI AUDITOR TERHADAP FINANCIAL DISTRESS - Ignasia Nathania Astria Gunawijaya (Jurnal Akuntansi Bisnis, 2015)
Financial distress is a problem for many companies. Financial distress will determine the reaction of investors to the relevant company. The objective of the study is to analyze the influences of audit committee characteristics, the independences of the board of commissioners, and auditor reputation on financial distress. The characteristics based on three parameters: the number of audit committee members, frequency of meetings of audit committee members, and financial or accounting competence of audit committee members. This study focus on financial reports and annual reports of listed manufacturing companies in Indonesia Stock Exhange (IDX) during 2011-2015. The data was collected by purposive sampling. This study used logistic regression analysis to examine five of independent variables on dependent variable. The results indicate the number of audit committee members and auditor reputation were negatively affected the financial distress in companies. While the independence of the board of commissioners, meeting frequency, financial or accounting competence were positively affected the financial distress in companies.